A comparative nutritional life cycle assessment of processed and unprocessed soy-based meat and milk alternatives including protein quality adjustment - Herrmann, Moritz; Mehner, Eric; Egger, Lotti; Portmann, Reto; Hammer, Laila; Nemecek, Thomas (Frontiers in Sustainable Food Systems, 2024)
Efforts towards sustainable food systems have stimulated the development of plant-based alternatives to meat and milk. However, the debate on the nutritional quality of (processed) plant products compared to animal products remains unresolved, and combined assessments are needed to assess the benefits and trade-offs of these products in future diets. Using life cycle assessment (LCA) combined with nutrient density measurements and the Digestible Indispensable Amino Acid Score (DIAAS), this case study evaluates different processing stages of soy-based products, including cooked soybeans, tofu, soy drink, and a processed soy-based meat analogue (SBMA) produced in Switzerland. The nutritional LCA (n-LCA) showed that the environmental impact of all soy-based meat alternatives was 4–20 times lower than that of beef, especially when locally sourced soy was used. The differences were smaller when compared to chicken meat. All soy-based products showed lower DIAAS compared to animal products, but the results from the combined n-LCA were always less favourable for animal products in this case study. Contribution analyses showed that despite the high level of processing, the raw materials contributed significantly to the environmental footprint of SBMA, exceeding 50% in some environmental impact categories. Moreover, comparisons within the soy-based alternatives revealed a lower environmental impact of the minimally processed products. The higher protein quality and quantity of the processed SBMA were not sufficient to offset its higher environmental impact in this case study. SBMA also contained highest level of sodium and saturated fatty acids, highlighting the need for careful food formulation. Overall, this study showed the potential of soy-based alternatives to meat and milk to reduce the environmental impact of food production while highlighting the importance of considering their nutritional quality and the role of processing. Overall, this research provides insight into the potential of plant-based alternatives to meat and milk for sustainable diets amid the global challenge of climate change and changing dietary patterns.